Doxorubicin-Induced Cardiotoxicity: A Comprehensive Update - Vasvi Bhutani; Fahimeh Varzideh; Scott Wilson; Urna Kansakar; Stanislovas S. Jankauskas; Gaetano Santulli (Journal of Cardiovascular Development and Disease)
Doxorubicin is an anthracycline chemotherapeutic that is widely used for treating various malignancies, including breast cancer, lymphomas, and sarcomas. Despite its efficacy, its clinical utility is limited by a well-documented risk of cardiotoxicity, which may manifest acutely or chronically. Doxorubicin works by intercalating DNA and inhibiting topoisomerase II, leading to DNA damage and cell death. However, this mechanism is not selective to cancer cells and can adversely affect cardiac myocytes. The introduction of doxorubicin into oncologic practice has revolutionized cancer treatment, but its cardiotoxic effects remain a significant concern. This systematic review aims to comprehensively examine the multifaceted impact of doxorubicin on cardiac structure and function through both preclinical and clinical lenses.